Marco legal del pago por servicios ambientales en Costa Rica - Cabrera Medaglia, Jorge (2018)
This article explains in detail the regulatory framework for Payment for Environmental Services in Costa Rica, including the main legal and institutional provisions related to this issue, as found in forest, biodiversity, public services and organic agriculture regulations. Some concluding remarks are presented on the most relevant reasons for the success of the PES system and its impact on biodiversity conservation and rural development.